2019
DOI: 10.1108/arla-04-2019-0099
|View full text |Cite
|
Sign up to set email alerts
|

Perceived value, satisfaction and future intentions in sport services

Abstract: Purpose The purpose of this paper is to analyze the role of brand-related variables as congruence and brand trust on the traditional model formed by perceived quality, perceived value (PV) and satisfaction, in order to compare predictive models for the variables of PV, satisfaction and future intentions of 683 users of sports services. Design/methodology/approach The analysis has been carried out using two different methodologies. First, three models have been proposed to be analyzed by hierarchical regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 59 publications
1
11
0
4
Order By: Relevance
“…Likewise, these different studies have focused on analyzing, through linear models, these perceptions, without considering if in a combinatorial way there are variables that explain the prediction of an outcome variable more broadly. Some authors have attempted to solve this lack of knowledge about the interaction of variables by combining methodologies, which is why studies such as those of Calabuig et al (2015) or Alguacil et al (2019) analyze the sports context by combining HRM and QCA. Specifically, the article by Alguacil et al (2019) analyses the future intentions of the users of sports services, where, as in this study, the importance of satisfaction and perceived value is confirmed, showing a direct influence on the regression models and also being part of some of the combinations that produce the expected results, as in our case, the improvement of future intentions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, these different studies have focused on analyzing, through linear models, these perceptions, without considering if in a combinatorial way there are variables that explain the prediction of an outcome variable more broadly. Some authors have attempted to solve this lack of knowledge about the interaction of variables by combining methodologies, which is why studies such as those of Calabuig et al (2015) or Alguacil et al (2019) analyze the sports context by combining HRM and QCA. Specifically, the article by Alguacil et al (2019) analyses the future intentions of the users of sports services, where, as in this study, the importance of satisfaction and perceived value is confirmed, showing a direct influence on the regression models and also being part of some of the combinations that produce the expected results, as in our case, the improvement of future intentions.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have attempted to solve this lack of knowledge about the interaction of variables by combining methodologies, which is why studies such as those of Calabuig et al (2015) or Alguacil et al (2019) analyze the sports context by combining HRM and QCA. Specifically, the article by Alguacil et al (2019) analyses the future intentions of the users of sports services, where, as in this study, the importance of satisfaction and perceived value is confirmed, showing a direct influence on the regression models and also being part of some of the combinations that produce the expected results, as in our case, the improvement of future intentions. This influence of satisfaction and perceived value on future intentions is a connection confirmed throughout the literature ( Chen and Chen, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this decision is influenced by experience, subjective perception of service (Westerbeek and Shilbury, 2003;Montesinos-Saura et al, 2018;Bi et al, 2019), and by cognitive and affective elements (Oliver, 1981). In this line, satisfaction is linked to behavioral future intentions and loyalty (Alonso-Dos-Santos and Pérez-Campos, 2015;Bernal-García et al, 2018;Alguacil et al, 2019) and creates less price-sensitive customers (Ko et al, 2010;Calabuig-Moreno et al, 2015;Montesinos-Saura et al, 2018). Matsuoka et al (2003) suggest that satisfaction has a strong effect on future intentions and the decision to attend other events.…”
Section: Conceptual Framework and Hypothesismentioning
confidence: 99%
“…In the service literature, understanding the relationship between quality, perceived value, satisfaction, and customer loyalty is a topic that has been analyzed in depth (Parasuraman et al, 1985(Parasuraman et al, , 1988Zeithaml et al, 1996). Sports services are the focus of many of these analyses within the field of sports management (Cronin et al, 2000;Hightower et al, 2002;Calabuig-Moreno et al, 2010;Ko et al, 2010;Theodorakis et al, 2013;Alguacil et al, 2019). Few, however, add to the study the role of emotions (Biscaia et al, 2012;Calabuig-Moreno et al, 2015;Crespo-Hervás et al, 2019), despite the fact that in sports services, emotions and feelings are important factors for participation and development (Pérez-Campos, 2010;Vacher et al, 2017;Crespo-Hervás et al, 2019).…”
Section: Introductionmentioning
confidence: 99%